2004
DOI: 10.1098/rstb.2004.1527
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of actomyosin interactions in relation to the cross-bridge cycle

Abstract: Transient kinetic measurements of the actomyosin ATPase provided the basis of the Lymn-Taylor model for the cross-bridge cycle, which underpins current models of contraction. Following the determination of the structure of the myosin motor domain, it has been possible to introduce probes at defined sites and resolve the steps in more detail. Probes have been introduced in the Dicytostelium myosin II motor domain via three routes: (i) single tryptophan residues at strategic locations throughout the motor domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 73 publications
(137 reference statements)
1
10
0
Order By: Relevance
“…Bulk biochemical experiments have measured rates of chemical reactions associated with motor proteins activity [28, 32, 129132]. The application of well-established chemical-kinetic methods that include stopped flow, isotope exchange, fluorescent labeling and temperature quenching, has shown that motor proteins catalytic activities involve a complex network of biochemical states and conformations [129,131], although for many myosins and kinesins motor proteins one or few dominating biochemical pathways related to ATP hydrolysis have been identified [28,32,64,129,130].…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Bulk biochemical experiments have measured rates of chemical reactions associated with motor proteins activity [28, 32, 129132]. The application of well-established chemical-kinetic methods that include stopped flow, isotope exchange, fluorescent labeling and temperature quenching, has shown that motor proteins catalytic activities involve a complex network of biochemical states and conformations [129,131], although for many myosins and kinesins motor proteins one or few dominating biochemical pathways related to ATP hydrolysis have been identified [28,32,64,129,130].…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…In vitro motility studies on myosin IIa isolated from single muscle fibers of patients carrying the E706K mutation clearly showed a marked reduction of speed [38]. Furthermore, studies on the motor function of E683K mutant myosin of Dictyostelium discoideum, which is equivalent to the human MyHC IIa E706K mutation, demonstrated a threefold reduction of the ATP hydrolysis step followed by the slower acto-myosin dissociation [87]. Consequently, these effects lead to a reduced velocity of contraction.…”
Section: Pathogenesismentioning
confidence: 99%
“…As is discussed by Sweeney & Houdusse (2004), the commonly occurring post-rigor state is likely to be the form of myosin that rapidly releases from actin after the rebinding of ATP at the end of the power stroke (for further discussion see Zeng et al 2004). (Rayment et al 1993a) shown as a ribbon diagram in the orientation it would take on binding to actin viewed (a) from the pointed (À)-end of the actin filament and (b) at right angles to the actin filament.…”
Section: The Myosin Cross-bridge (A) Morphology and Classificationmentioning
confidence: 99%